The influence of nutritional status on complications after major intra abdominal Surgery. - Hannan, MA; Ali, Md Nowshad; Rahman, ANM Zia Ur; Basak, PM; Das, CK (TAJ: Journal of Teachers Association, 2018)
Background: Malnutrition is an impairment of health resulting from a deficiency or imbalance of nutrients, are associated with alteration in cellular physiology and organ function, which are of importance for the surgical patients. Protein energy malnutrition is a known clinical problem in hospital has an important role on post operative outcome so that necessary measures can be taken to improve nutritional status of these patients and improve post operative outcome. Objective: The objectives of this study are to assess the relation of nutritional status with post operative complications following major intra-abdominal surgery and to find out the complications in a malnourished patient. Method: This is prospective descriptive Study. The sample for the study constituted 100 randomly selected of major intra abdominal surgery age ≥12 yrs which was admitted the surgical word of SSMC& Mitford Hospital, Dhaka from May 2010 to October 2010 as a case of elective abdominal surgery. Result: Higher Prevelence of malnourished was found among elective surgical patient that about 48-57%. Regearding pattern of post operative complication among malnourished patent pulmonary complication 15.3% (Average 11%) Wound infection 17% (Average 12%) Brust abdomen 2.8% (Average 4.1%) Excess duration of Hospital Stay in melnutrited group than the Nutritionally Sound gorup was about 11 days. Conclusion: There is significant number of surgical patient suffering from diferent type of Nutritional imbalance. Due attention should be given to improve nutritional status of a patient before any major intrabdominal surgery. TAJ 2014; 27(2): 6-10